Development of tifa based worksheet to improve sound conceptual understanding - Kaleb A Yenusi; Iriwi L.S Sinon; Asiroha Siboro; Merry C.H. Rumainum; Mujasam (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2026)
This study responds to the limited availability of ethnocontextual worksheets on the topic of sound in junior high school by developing a contextual learning worksheet based on the traditional Papuan musical instrument Tifa. Using the ADDIE Research and Development model, the worksheet was validated by material and media experts and tested on 27 eighth-grade students. The combined results of the validation, practicality, and effectiveness assessments indicate that the worksheet meets the criteria of being valid, practical, and effective, with a notable improvement in students’ conceptual understanding. The findings demonstrate how integrating Papuan cultural instruments can function as a culturally responsive learning medium in physics education, connecting scientific concepts with local cultural knowledge. Therefore, the developed worksheet is suitable for classroom implementation and contributes to promoting culturally grounded and meaningful physics learning